Pengaruh Lingkungan Kerja dan Pengembangan Karir Terhadap Kinerja Karyawan PT Pelangi Inti Pertiwi Musi Banyuasin - Romansah, Dedi; Yanti, Siti Komariah Hilda; Kurniawan, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study discusses the influence of the work environment and career development on employee performance. The purpose of this study was to analyze the influence of the work environment and career development on the performance of employees at PT. Pelangi Inti Pertiwi Musi Banyuasin either partially or simultaneously. This type of research is descriptive quantitative. The sampling technique used the census method with a total sample of 93 employees of PT. Pelangi Intiwi Pertiwi Musi Banyuasin. Data analysis test using SPSS version 25. The results showed that the work environment has a positive and significant effect on employee performance. This can be seen in the calculated t value of 3,127 with a significance (0.002 <0.05). Career development has a positive and significant effect on employee performance. This can be seen in the calculated t value of 6,636 with a significance (0.000 <0.05). The results of the tests that have been carried out get a calculated F value of 40,315 > F table 2.70 so that it can be concluded that the work environment and career development simultaneously influence employee performance. The coefficient of determination (R2) is 47.30%, while the remaining 52.70% is influenced by other variables that have not been examined.